Modeling, design, and simulation of a radio frequency microelectromechanical system capacitive shunt switch - Jmai, Bassem (2018)
This tutorial paper presents an empirical model of a capacitive radio frequency microelectromechanical system switch in the microwave domain. The simulation results of the mechanical and electrical aspects of the proposed model were computed with Matlab. The mechanical modeling is validated by COMSOL software through the finite element method to determine the spring constant and the necessary applied voltage. The electromagnetic simulation results are validated by 3 different software: the High‐Frequency Structure Simulator based on the finite element method, the Computer Simulation Technology based on finite integration technique method, and the Advanced Design System based on the method of moments. The obtained results are performed in both down (OFF) and up (ON) states in the frequency range of 1 to 40 GHz, and the considered performance benchmarks are the insertion loss, return loss, isolation, and phase.